Adenolipoleiomyoma Polyp of the Uterus: A Case Report and Review of the Literature. (6th September 2018) - Catteau, Xavier; Anaf, Vincent; Noël, Jean-Christophe
Abstract : Adenolipoleiomyoma is a very rare lesion of the uterus. Only four cases were reported. We describe one case of adenolipoleiomyoma presenting as a polyp in a postmenopausal woman with menorrhagia. Adenolipoleiomyoma is a very rare lesion and the histogenesis remains unclear. We discuss the origin and the differential diagnosis of this lesion.